Radiological Fusion Criteria of Postoperative Anterior Cervical Discectomy and Fusion: A Systematic Review. Issue 7 (October 2018) - Oshina, Masahito; Oshima, Yasushi; Tanaka, Sakae; Riew, K. Daniel
Study Design: Systematic review. Objectives: Diagnosis of pseudarthrosis after anterior cervical fusion is difficult, and often depends on the surgeon's subjective assessment because recommended radiographic criteria are lacking. This review evaluated the available evidence for confirming fusion after anterior cervical surgery. Methods: Articles describing assessment of anterior cervical fusion were retrieved from MEDLINE and SCOPUS. The assessment methods and fusion rates at 1 and 2 years were evaluated to identify reliable radiographical criteria. Results: Ten fusion criteria were described. The 4 most common were presence of bridging trabecular bone between the endplates, absence of a radiolucent gap between the graft and endplate, absence of or minimal motion between adjacent vertebral bodies on flexion-extension radiographs, and absence of or minimal motion between the spinous processes on flexion-extension radiographs. The mean fusion rates were 90.2% at 1 year and 94.7% at 2 years. The fusion rate at 2 years had significant independence ( P = .048). Conclusions: The most common fusion criteria, bridging trabecular bone between the endplates and absence of a radiolucent gap between the graft and endplate, are subjective. We recommend using <1 mm of motion between spinous processes on extension and flexion to confirm fusion.